The application of Internet Of Things (IoT) to the traditional power grid - Morshed, Ragib; Ahmed, Fabliha Lamisa (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.